Against Digital Extinction: Cyber Peace - Gençoğlu, Muharrem Tuncay (My University, 2021)
At a time when cyberattacks are becoming a part of our daily lives and small-scale attacks are becoming commonplace, it is obvious that digital infrastructures are widely and intensely used in our lives and that they can be used for hostile, non-peaceful purposes. This situation has become very serious especially for Turkey, due to the complex attacks taking place around the World. The issue of cybersecurity around the world is not limited to certain cyberattacks but also brings the threat of these attacks turning into comprehensive cyber warfare. Therefore, the more important the security of the geographical borders, the more important the security of electronic systems and the data stored there. Since the most important component of security is peace, it is worth examining as a very important concept in Cyber Peace in response to the negative perceptions of cyberwar, cyber terrorism and cybercrime. This study, it is aimed to create a conceptual basis of cyber peace and contribute to this field to create a defense mechanism based on peaceful behaviors in cyberspace. For this purpose, the definition of cyber peace has been made, and it has been focused on establishing and protecting cyber peace. It was emphasized that cyber peace can be sustainable not through disarmament, but by reducing the risk through modernization of attack and defense capacities. In this study, which we do not have much work on cyber peace and we can accept it as the first step in filling this gap; It was concluded that private and voluntary organizations must take a more active role in protecting cyber peace.
Keywords: Peace; Cyber Peace; Cyber Peace Protection; Cyber.